2016
DOI: 10.1002/etc.3267
|View full text |Cite
|
Sign up to set email alerts
|

Critical perspectives on mercury toxicity reference values for protection of fish

Abstract: Environmental management decisions at mercury-contaminated sediment sites are predicated on the understanding of risks to various receptors, including fish. Toxicity reference values (TRVs) for interpreting risks to fish have been developed to assess mercury concentrations in fish or fish prey. These TRVs were systematically evaluated based on several lines of evidence. First, their conceptual basis and specific derivation were evaluated, including a close review of underlying toxicity studies. Second, case st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 111 publications
(344 reference statements)
2
11
0
Order By: Relevance
“…Sulfur deposition is relevant because it contributes to increases in Hg methylation and subsequent bioaccumulation [115]. These lines of evidence indicated that average naturally occurring Hg concentrations in forage fish are roughly 0.03 mg/kg to 0.1 mg/kg, with greater concentrations (on the order of 0.1-0.3 mg/kg) expected in predatory fish [155]. By this estimate, all of the previously published diet-based avian TRVs for Hg are similar to or lower than naturally occurring Hg concentrations in fish.…”
Section: Diet-based and Dose-based Trvsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sulfur deposition is relevant because it contributes to increases in Hg methylation and subsequent bioaccumulation [115]. These lines of evidence indicated that average naturally occurring Hg concentrations in forage fish are roughly 0.03 mg/kg to 0.1 mg/kg, with greater concentrations (on the order of 0.1-0.3 mg/kg) expected in predatory fish [155]. By this estimate, all of the previously published diet-based avian TRVs for Hg are similar to or lower than naturally occurring Hg concentrations in fish.…”
Section: Diet-based and Dose-based Trvsmentioning
confidence: 99%
“…Because Hg is naturally occurring (e.g., in volcanic eruptions, natural seeps, geological deposits) and bioaccumulative, there must be a lower limit to the Hg concentrations in prey that could plausibly harm bird populations; that is, TRVs should not be lower than naturally occurring Hg concentrations in the normal prey of the bird species being assessed. However, as reviewed by Fuchsman et al , it is challenging to define naturally occurring Hg concentrations in fish and other avian prey, because Hg released by humans to the environment over centuries has become globally distributed. Fuchsman et al evaluated 3 lines of evidence relevant to estimating natural background Hg concentrations in prey fish: a modeling exercise by Hope and Louch , Hg concentrations in control fish from toxicity experiments , and Hg concentrations in fish collected from areas minimally impacted by anthropogenic increases in aerial deposition of Hg and sulfur .…”
Section: Comparison With Existing Trvsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beckvar et al (2005) discuss various approaches to linking whole-body fish tissue residues to potential biological effects (relative to Hg and DDT) and weigh the technical advantages of each. Fuchsman et al (2016) reviewed the various proposed toxicity reference values for Hg (based on adverse effects to fish) and found that many of these represent ambient or "background" concentrations. Thus, selecting LOAEL values as toxicity benchmarks for environmental receptors involves uncertainty.…”
mentioning
confidence: 99%
“…Beckvar et al () discuss various approaches to linking whole‐body fish tissue residues to potential biological effects (relative to Hg and DDT) and weigh the technical advantages of each. Fuchsman et al () reviewed the various proposed toxicity reference values for Hg (based on adverse effects to fish) and found that many of these represent ambient or “background” concentrations. Thus, selecting LOAEL values as toxicity benchmarks for environmental receptors involves uncertainty.…”
mentioning
confidence: 99%